Social innovations for the achievement of competitive agriculture and the sustainable development of peripheral rural areas - Jadranka Deže; Tihana Sudarić; Snježana Tolić (Economies, 2023)
The purpose of the study was to analyze social innovations in a broader context in order to achieve sustainable development goals. In terms of a response to the research questions, a comprehensive analysis of an alteration process in rural development was conducted while identifying the social innovations, highlighting the good practices, and conceptualizing the social innovation typology of peripheral rural areas. The methodology included a comparative analysis addressing three European regions, namely Northern, Central, and Western Europe, represented by Finland, Croatia, and France, respectively, together with their nine good practice examples during a biennial RUR'UP project period. The results demonstrate the typological differences between the selected examples of social innovations that stimulate the rural development of peripheral rural areas. These examples were formulated by the different social conditions in which these innovations were created. As a traditional economic activity in rural areas, agriculture is a great challenge for the application of innovations, can effectuate changes in the economic activities of the rural population, and can promote social and economic sustainability. In conclusion, significant differences among the regions were proven on the basis of social, environmental, and economic impacts arising from the application of social innovation.
Keywords: 330; agriculture; peripheral rural areas; social innovations; sustainable development